Examination of the Relationships between Internal and External Egg Quality Traits: A Structural Equation Model - Samet Hasan Abacı; Taner Tunç; Hasan Önder; Kadir Erensoy; Musa Sarıca (Turkish Journal of Agriculture: Food Science and Technology, 2023)
This study aimed to determine the structural relationship between internal and external egg quality (IEEQ) traits. In this study, 114 eggs produced from 24 weeks-old laying hens reared at the Ondokuz Mayis University Research Farm were used. Egg weight (EW), egg width (EWi), egg length (EL) and shell weight (SW) measurements were examined as external quality traits. Also, albumen height (AH), albumen width (AW), yolk height (YH), yolk weight (YW) and yolk diameter (YD) parameters were used as internal quality traits. Structural Equation Model (SEM) was used to determine the relationships between IEEQ traits. Data analysis was performed with the LISREL package. It has been determined that the variables that are important in determining the external egg quality are SW, EWi and EL. When the variables explaining the internal traits were examined, it was determined that the YW, YD, AW, AH and YH were significant. It was determined that the relationship between external egg quality and internal quality was 0.96 and external quality explained the internal quality by 91%. It has been determined that the SEM used in this study is sufficient to explain the relationship between internal and external quality.